Is Academic Achievement Influenced by Self-Esteem, Loneliness, and Internet Addiction? - Wahyu Rahardjo; Matrissya Hermita; Nurul Qomariyah; Inge Andriani Andriani (Universitas Ciputra Surabaya, 2023)
The purpose of this study is to measure whether self-esteem, loneliness, and internet addiction affect academic achievement in college students empirically. This study involved 369 students who actively used the internet in the Greater Jakarta area and several other cities in Indonesia. Structural equation modeling (SEM) is used to analyze the theoretical model. The findings of this research show that the empirical model is fit with data, and self-esteem, loneliness, and internet addiction affect academic achievement in college students simultinously. However, the influence partially shows that self-esteem has no direct influence on academic achievement, but it has strong negative influence to loneliness and internet addiction. Loneliness has negative influence to academic achievement. The other result also show that internet addiction has positive effect to academic achievement.